Acoustic Emission in a Laboratory: Mechanism of Microearthquakes Using Alternative Source Models. Issue 6 (14th June 2018) - Petružálek, M.; Jechumtálová, Z.; Kolář, P.; Adamová, P.; Svitek, T.; Šílený, J.; Lokajíček, T.
Abstract: Here a shear‐tensile crack (STC) model is presented as suitable for acoustic emission (AE) events. Experimental data were obtained from a uniaxial compression test performed on a Westerly Granite specimen using a 14‐channel AE monitoring system. The advantages of the STC versus a traditional MT (moment tensor) approach are as follows: (i) it is a physical source, contrary to the MT, since the STC describes the straight and simple fracture modes anticipated inside a loaded sample, namely, the shear slip and both the opening and closing tensile cracks; and (ii) it is simpler because it is described by fewer parameters (five instead of the six required for an unconstrained MT), which is essential for solving the inverse problem. The presented STC procedure was tested on 38 AE events selected over a range of 50–98% for the uniaxial compressive strength. As compared to the MT model, the STC model displayed a similar fit for input data while providing far smaller confidence regions. The results indicate a more certain determination for the mechanism of orientation and improved reliability for the decomposition components. In addition, use of STC model allowed better distinction between tension and shear type for AE events, which may be crucial for recognizing an approaching failure. For our experiment, application of the STC model proved to be useful for recognizing the threshold of unstable microcracking and indicative for determining the failure plain orientation. Plain Language Summary: Fractures created during loading of a rock sample in a laboratory are proxies of earthquakes in a macro scale, both natural and induced ones. Acoustic emission accompanying the events is an analogy of seismic wave radiation from the earthquake focus. The mechanism of the focus—in simple words the description of the rock mass movement on the fault—demands for the monitoring well around the focus. This is often not the case in both the macro and laboratory scales. Then, instead of the traditional source model, it is useful to apply a simpler one, which makes the inversion task more feasible. Following this approach, we processed acoustic data of 38 microearthquakes originated by loading of a sample from Westerly Granite and obtained a good relevance of their mechanisms to the macroscopic failure plane. With the source model suggested, it is easier to recognize the fracture modes occurring in the microearthquake foci, that is, to discern between shear (tangential) slips on faults/planes of weaknesses and tensile cracks, in other words, between a change of shape and a change of volume. The task is important, for example, in assessing the permeability changes in oil/gas and geothermal reservoirs. Key Points: As compared to the MT, the STC improved reliability of mechanism orientation and moreover the decomposition into shear versus nonshear parts Largest AE events indicated a transition from tension to shear microcracking when crossing the crack damage threshold Preferential orientation of the shear cracks was determined to coincide with the orientation of the failure plane